Deteksi Kerapatan Vegetasi Dan Suhu Permukaan Lahan Kabupaten Banyuwangi Menggunakan Citra Landsat 8-Oli (Studi Kasus Tahun 2023) - Khoirunnisa, Arini; Wesnawa, I Gede Astra; Citra, I Putu Ananda; Dwipayana, Made (Innovative: Journal Of Social Science Research, 2024)
This research was conducted in Banyuwangi Regency. Environmental and land conditions in this district are undergoing significant changes along with population growth and human activities. These changes include land use change from natural vegetation to settlements, industry and infrastructure. This research is a descriptive investigation that focuses on the processing results of Landsat 8 images that have been acquired and processed in the form of land surface temperature maps and vegetation density maps in the form of NDVI and supported by geological data and manifestations in the Banyuwangi Regency area. This research aims to (1) Analyze vegetation density in the form of NDVI from the processing of Landsat 8 satellite images in the Banyuwangi Regency area, and (2) Analyze land surface temperature in the form of a land surface temperature map from the processing of Landsat 8 satellite images in the Banyuwangi Regency area. To answer the objectives, investigative research was conducted. Data were collected using survey and direct measurement methods. The results show that vegetation density in Banyuwangi Regency is dominated by vegetation density with the non-vegetated class being the NDVI class which has the largest area reaching 124,014.04 hectares. Land surface temperature in Banyuwangi Regency from Landsat 8 image extraction obtained the highest temperature in the LST 35-<40 class reaching 15,752.07 hectares and the lowest temperature in the LST 10-15 class reaching 43,228.96 hectares.